Employee empowerment practice for sustainable manufacturing performance: mediating role of quality of work life - Imran, Amina (2018)
Stakeholders are consistently pressurizing manufacturers to integrate the social and environmental factors within their production process to protect the society and environment from the negative effects of the manufacturing process As a result, manufacturing processes experience continuous adaptation that significantly reshaped employee work practices. The literature on identification of the employee work practice that can enhance sustainable manufacturing performance is limited. Literature identified employee empowerment practice not only enhances sustainable manufacturing performance (SMP), but also the quality of work life (QWL). However, few studies have attempted to empirically test the relationship between the employee empowerment, quality of work life and sustainable manufacturing performance. The current study focused on the investigation of the relationship between employee empowerment and sustainable manufacturing performance, and the mediating role of the quality of work life was also investigated. Sustainable manufacturing performance was measured on the basis of social, economic and environmental dimensions. A quantitative research design was used to address the problem. A systmatic random sample of 200 employees from 30 large manufacturers in Malaysia was used to collect data on a 5-point likert scale adapted questionnaire. Furthermore, this data was statistically tested using Smart PLS (SEM) for empirical investigations of the relationships between employee empowerment, quality of work life and sustainable manufacturing performance. The result confirmed the positive relationship between employee empowerment and sustainable manufacturing performance and the mediating role of quality of work life between the relationship of employee empowerment and sustainable manufacturing performance. In conclusion studt recomends organizations to encourage employees to be involved in the decision making process regarding social, economic and environmental factors in order to enhance sustainable manufacturing performance and their quality of work life.